Varus thrust during walking and the risk of incident and worsening medial tibiofemoral MRI lesions: the Multicenter Osteoarthritis Study. Issue 6 (June 2017) - Wink, A.E.; Gross, K.D.; Brown, C.A.; Guermazi, A.; Roemer, F.; Niu, J.; Torner, J.; Lewis, C.E.; Nevitt, M.C.; Tolstykh, I.; Sharma, L.; Felson, D.T.
Summary: Objective: To determine the association of varus thrust during walking to incident and worsening medial tibiofemoral cartilage damage and bone marrow lesions (BMLs) over 2 years in older adults with or at risk for osteoarthritis (OA). Method: Subjects from the Multicenter Osteoarthritis Study (MOST) were studied. Varus thrust was visually assessed from high-speed videos of forward walking trials. Baseline and two-year MRIs were acquired from one knee per subject and read for cartilage loss and BMLs. Logistic regression with generalized estimating equations was used to estimate the odds of incident and worsening cartilage loss and BMLs, adjusting for age, sex, race, body mass index (BMI), and clinic site. The analysis was repeated stratified by varus, neutral, and valgus alignment. Results: 1 007 participants contributed one knee each. Varus thrust was observed in 29.9% of knees. Knees with thrust had 2.17 [95% CI: 1.51, 3.11] times the odds of incident medial BML, 2.51 [1.85, 3.40] times the odds of worsening medial BML, and 1.85 [1.35, 2.55] times the odds of worsening medial cartilage loss. When stratified by alignment, varus knees also had significantly increased odds of these outcomes. Conclusion: Varus thrust observed during walking is associated with increased odds of incident and worsening medial BMLs and worsening medial cartilage loss. Increased odds of these outcomes persist in varus-aligned knees.